Gap-mode plasmons at 2 nm spatial-resolution under a graphene-mediated hot spot. (June 2022) - Zhang, Fan-Li; Yi, Jun; Lin, Weiyi; You, En-Ming; Lin, Jia-Sheng; Jin, Huaizhou; Cai, Weiwei; Tian, Zhong-Qun; Li, Jian-Feng
Abstract: Fully understanding the properties of plasmonic nanocavity would boost the spectral detection technologies based on plasmons. Recent efforts are mainly focused on the light-matter interactions, which greatly facilities the cognition for nano-optics in the hot spot. However, realizing the high spatial resolution of vertical plasmons in the specific plasmonic nanocavity has been elusive to date. Herein, the monolayer graphene-mediated plasmonic nanocavity has been constructed, which proves the nanoscale inhomogeneity of the enhanced electromagnetic field distribution. Via sandwiching the graphene monolayer at various positions insider fixed nanocavity, we also successfully and quantitatively elucidate the spatial-dependent resonance of the cavity plasmon mode with a resonance spectral shifts down to ca. 4.43 Ångstrom/nm. Simultaneously, the experimental results and theoretical calculation illustrate the correlation between the near field and far field in the hot spot, which also provides a novel strategy for manipulating the light-matter interactions at the nanoscale and graphene nano-devices fabrication based on plasmons. Graphical Abstract: The well-defined graphene-mediated plasmonic nanocavity was fabricated, and we have successfully elucidated the spatial-dependent resonance of the cavity plasmon mode with a spatial resolution down to sub-2 nanometer and correlate near and far-field effectively. ga1 Highlights: Plasmonic hot spot fabrication and controllable plasmon modes with precise gap spacer. Monolayer graphene sandwiched in the plasmonic nanocavity serves as a probe to detect the gap-mode plasmons. The near and far-field responses based on graphene-mediated plasmonic nanocavity are correlated effectively.